Mandatory notice and layoff, job search, and efficiency - Jonas Cederlöf; Peter Fredriksson; Arash Nekoei; David Seim (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2024)
In all OECD countries, Mandatory Notice (MN) policies require firms to inform workers in advance of a layoff. In our theoretical framework, MN helps workers avoid unemployment and find better jobs by encouraging workers to search for a new job while still employed, thereby increasing future production. The magnitude of this production gain depends on the relative effectiveness of search while employed versus unemployed. But on-the-job search and diminished work incentives reduce current production. If future gains outweigh current production losses, longer advance notice improves production efficiency. If not, Coasian bargaining predicts that firms offer a larger severance instead of longer notice. With bargaining, the sole efficiency loss of MN is due to delayed separations of unproductive job matches. We test these predictions using novel Swedish administrative data on layoff notifications. Workers eligible for extended MN receive longer notice and larger severance, resulting in less exposure to non-employment spells and higher-paying jobs. These favorable labor market outcomes are solely due to longer notice; in contrast, larger severance delays job finding and has no impact on wages. We also show that advance notice replaces job search while unemployed with more effective search while employed. On the production side, we document a productivity drop among notified workers and estimate a production loss due to delayed separations. Using our estimates of production gains and losses to evaluate the overall production efficiency, we conclude that the gains of MN seem to outweigh the losses.
Keywords: J31; J33; J63; J68; 330; Advance notice; Job search; Layoff; Job quality